DENSITY AND DISTRIBUTION OF Chiridota rotifera (POURTALÈS, 1851) (ECHINODERMATA: HOLOTHUROIDEA: CHIRIDOTIDAE) ON PACHECO BEACH, CEARÁ STATE - Martins, Ana Carolina; Martins, Inês Xavier; Cascon, Helena Matthews (Arquivos de Ciências do Mar, 2010)
The population density and distribution of Chiridota rotifera on Pacheco Beach, Caucaia, Ceará was investigated in the present study. Sampling was performed from October to December, 2002, and April to July, 2003, using three transects, each 120 m long, from the intertidal to the subtidal zone. The number of individuals was counted with 0,25 m 2 quadrats, and the distribution pattern of specimens was analyzed with the Morisita index. The mean density was 0,8 ind.m - ². The difference between rainy and dry seasons densities was non significant (p>0.05). A significant difference on the placement of the specimens in relation to the shoreline during the two seasons was observed (p<0.05), with the specimens being found closer to the shoreline during the rainy season. The studied population showed an aggregate distribution